Les appellations de la Zoarces viviparus et de la Lumpenus lampretaeformis dans les dialectes et la langue écrite du finnois - Uusitalo Harri (France, 2025)
The viviparous eelpout (Zoarces viviparus) and the snakeblenny (Lumpenus lampretaeformis) are species of fish that live in the Baltic Sea. This lexicological study focuses on the Finnish names of both species in written language and in dialects. The oldest written names are from the 18th century, and the study shows the diachronic and regional variation of names in all their diversity. In addition, the perspectives of word formation and naming motivation are examined. The results show how the Finnish names for the viviparous eelpout and snakeblenny were established over time. The variation has been substantial and the establishment of this variation was intentional. The two species are studied together because they have a connection related to the variation of their Finnish names.